IMPULSIVE BUYING PADA FANS K-POP DI TWITTER - Asra Faiza Khairunnisa; Aditya Nanda Priyatama; Selly Astriana (Program Studi S1 Psikologi, 2021)
One of the phenomena that has arisen due to the impact of globalization is the emergence of the Korean Wave which has been familiarly felt since the early 2000s in Indonesia, until now creating a new culture in which a lot of merchandise is traded as a form of identity for K-Pop group. In this study, we explore the relationship between celebrity worship, self-regulation and impulsive buying on merchandise purchases by K-Pop fans which has become a culture for fans community for the past decade. Sample of this research is K-Pop band ‘Day6’ fansclub community from Solo, MyDaySolo with total of 67 respondents. The sampling method used is purposive sampling with a few criterias needed. This research is conducted with quantitative approach using multiple regression analysis. The results indicate that there is a relationship between celebrity worship, self-regulation, and impulsive buying shown by the result of multiple regression analysis which is F = 60,982 (p<0,05). Keywords: Impulsive buying, celebrity worship, self-regulation, K-Pop fans